1990
DOI: 10.1111/j.1476-5381.1990.tb14651.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Ca2+ antagonists and hydralazine on central 5‐hydroxytryptamine biochemistry and function in rats and mice

Abstract: 1 The effects of calcium antagonists on behaviour mediated by 5-hydroxytryptamine (5-HT) have been studied in rats and mice together with an investigation of the effects of these drugs on 5-HT synthesis in rat brain and endogenous 5-HT release from brain slices. 2 Administration of felodipine (35mg kg-i.p.) to rats pretreated with tranylcypromine (20mg kg-1, i.p.) resulted in the animals displaying the complete 5-HT-mediated behavioural syndrome (including head weaving, reciprocal forepaw treading and hind lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This result indicates an inhibitory effect on the antidepressant effect of sertraline by repeated doses of nimodipine administration. The inhibition revealed by repeated doses of nimodipine administration may be the consequence of the reported role of L-type calcium channels on the release of neurotransmitters [18] and the complex effects of ccas on serotonin functions in rodents [19]. In this study, we also observed that there was no significant difference between groups in the time spent in closed arms in the elevated plus maze test.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This result indicates an inhibitory effect on the antidepressant effect of sertraline by repeated doses of nimodipine administration. The inhibition revealed by repeated doses of nimodipine administration may be the consequence of the reported role of L-type calcium channels on the release of neurotransmitters [18] and the complex effects of ccas on serotonin functions in rodents [19]. In this study, we also observed that there was no significant difference between groups in the time spent in closed arms in the elevated plus maze test.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, Srivastava et al and aburawi et al did not use nimodipine in their study, instead they used nifedipine as an L-type dihydropyridine derivate cca. although both nifedipine and nimodipine are dihydropyridine derivate L-type ccas, they may have different effects on neurotransmitter functions [19].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also reported that dihydropyridines exert complex changes in 5-HT function. Recently, Green et al(1990) indicated that pretreatment of rats with felodipine. 15 min before tranylcypromine.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT 2A receptor binding assay was done according to the modified procedure of Green et al [22]. The brain stem was homogenized in 10 volumes of ice cold 0.32 M sucrose in Potter-Elvejhem homogeniser.…”
Section: -Ht 2a Receptor Analysismentioning
confidence: 99%